Revolutionary bamboo crash barriers utilizing sustainable materials for enhanced road safety - N. Jiyas; Indu Sasidharan; K. Bindu Kumar (Scientific Reports)
Abstract Road accidents are a growing concern worldwide, and crash barriers have significantly reduced the severity of these incidents. In its pursuit of developing an eco-friendly crash barrier, India installed the world’s first 200 m bamboo crash barrier, on Bombay–Pune Highway. Although its eco-friendly and recyclable design is commendable, using Bambusa balcooa infused with creosote oil and covered with High-density polyethylene (HDPE) raises substantial health and environmental issues due to the presence of toxic and carcinogenic Polycyclic aromatic hydrocarbons (PAHs). To address these concerns, a novel eco-friendly design has been proposed, utilizing Pseudoxytenanthera bamboo species treated with Cashew nutshell liquid (CNSL). This study rigorously characterizes these bamboo species through mechanical testing at both nodes and internodes, evaluating critical strength parameters such as axial tensile modulus, ultimate strength, compression strength, flexural strength, and impact strength. Scanning electron microscopy is employed to examine fracture morphology, linking the natural fiber characteristics to their mechanical properties. The results indicate that Pseudoxytenanthera stocksii exhibits superior Tensile strength (496.73 MPa), flexural (235.57 MPa), Impact strength (4.8 kJ/m2) and compressive strength (68.66 MPa), with a direct correlation between density, particularly in nodal regions. The final phase involves chemically validating the bamboo treated with CNSL to enhance its environmental friendliness, presenting a viable alternative to steel for sustainable infrastructure. This study presents a high-strength sustainable and non-toxic alternative to conventional crash barriers by utilising Pseudoxytenanthera bamboo species treated with CNSL, replacing the toxic creosote-treated Bambusa balcooa, and offering a robust solution for safer road infrastructure while advancing green engineering practices.